Bird Theatre - BBC (London, United Kingdom BBC Children's Books, 2009)
this is a new "3rd & Bird" storybook, based on an episode from the new TV series. Samuel and Rudy are rehearsing for Mr Beakman's play. Muffin wants to be in the play too, but there is no part for her - that is until all the props blow away. Muffin steps in and becomes the star of the play.
Keywords: Read Aloud -- Read Aloud